2010
DOI: 10.1007/s11664-010-1076-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Thermoelectric Properties of LiAlSi and LiAlGe

Abstract: The compounds LiAlSi and LiAlGe were synthesized and their thermoelectric properties and temperature stability were investigated. The samples were synthesized by arc melting of the constituent elements. For the determination of the structure type and the lattice parameter, x-ray powder diffraction was used. Both compounds were of the C1 (b) structure type. The stability of the compounds was investigated by differential thermal analysis and thermal gravimetry. The Seebeck coefficient and the electrical resistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
(12 reference statements)
1
21
0
Order By: Relevance
“…The present work only deals with quaternary equivalents of transition-metal-based half-Heusler compounds with 18-valence electrons. The concepts discussed here are easily applicable to other multi-component Heusler-based structures, 43 such as 8-electron Nowotny-Juza phases (e.g., LiAlSi), 44,45 f-block element-based half-Heuslers (e.g., DyNiBi), 46 24electron full-Heuslers (e.g., VFe 2 Al), 30,47,48 and Li-based 18-electron Heuslers, 49 opening up the possibility for an even larger phase space of materials with versatile properties.…”
Section: Valence Balanced Rule As a Dependable Strategy For Discovery Of Low K L Quaternary Half-heuslersmentioning
confidence: 99%
“…The present work only deals with quaternary equivalents of transition-metal-based half-Heusler compounds with 18-valence electrons. The concepts discussed here are easily applicable to other multi-component Heusler-based structures, 43 such as 8-electron Nowotny-Juza phases (e.g., LiAlSi), 44,45 f-block element-based half-Heuslers (e.g., DyNiBi), 46 24electron full-Heuslers (e.g., VFe 2 Al), 30,47,48 and Li-based 18-electron Heuslers, 49 opening up the possibility for an even larger phase space of materials with versatile properties.…”
Section: Valence Balanced Rule As a Dependable Strategy For Discovery Of Low K L Quaternary Half-heuslersmentioning
confidence: 99%
“…SiAlLi and GeAlLi have also been previously synthesized and their thermoelectric properties investigated. 84,85 Very high ZT was not found experimentally. However, the present results in combination with the existing experimental data suggest further investigation and optimization of those compounds.…”
Section: Electronic Transportmentioning
confidence: 97%
“…Joachim Barth et al [10] studied the Seebeck coefficient and the resistivity of LiAlSi and LiAlGe compounds in the temperature range from 2 K to 650 K. They found a maximum value of the Seebeck coefficient at a temperature of 400 K for LiAlSi compound, and small thermal conductivity for LiAlGe. Finally they concluded that the LiAlSi is more promising of the two compounds.…”
Section: Introductionmentioning
confidence: 99%